Optical coherence tomography surpasses fundus imaging and intracranial pressure measurement in monitoring idiopathic intracranial hypertension - Yumin Huang-Link; Sanna Eriksson; Jan Schmiauke; Ursula Schmiauke; Mats Fredrikson; Max Borgström; Ge Yang (Scientific Reports)
Abstract We aim to evaluate the retinal nerve fiber layer (RNFL) thickness measured with optical coherence tomography (OCT) in comparison with papilledema grade, and to assess the relationship between RNFL thickness, papilledema grade, and intracranial pressure (ICP) in idiopathic intracranial hypertension (IIH). Sixty-five patients with active IIH (AIIH) with papilledema, 39 with chronic IIH (CIIH) without papilledema and 80 healthy controls (HC) were examined with OCT and fundus imaging. RNFL thickness, papilledema grade and ICP level were assessed in 55 with AIIH and 26 with CIIH. RNFL thickness was significantly higher in AIIH compared to CIIH or HC. RNFL thickness correlated strongly with papilledema grade (coefficient 0.78, p < 0.01) and moderately with ICP (coefficient 0.569, p < 0.01). RNFL thickness was associated with papilledema progression (R2 = 0.656, p < 0.01): specifically, with increases of 9 µm from normal to mild grade (p > 0.05), 91 µm from normal to moderate (p < 0.01), and 214 µm from normal to severe (p < 0.01). ICP showed a weaker correlation with papilledema grades (R2 = 0.339, p < 0.05), with significant increase (8 cm H2O, p < 0.01) only from normal to severe papilledema. RNFL correlated strongly with papilledema grade and moderately with ICP levels. RNFL thickness increased proportionally per papilledema grade.